Iron(iii) oxyhydroxide and oxide monoliths with controlled multiscale porosity: synthesis and their adsorption performance. Issue 19 (30th April 2018) - Hara, Yosuke; Kanamori, Kazuyoshi; Morisato, Kei; Miyamoto, Riichi; Nakanishi, Kazuki
Abstract : Iron(iii ) oxyhydroxide and oxide monoliths with controlled multiscale porosity have been successfully fabricated via the sol–gel process accompanied by phase separation. Abstract : Iron(iii ) oxyhydroxide and oxide monoliths with controlled multiscale porosity have been successfully fabricated via the sol–gel process accompanied by phase separation. The size of macropores was controlled by synthesis parameters such as starting compositions. The as-dried iron(iii ) oxyhydroxide monoliths were amorphous and possessed surface areas over 340 m 2 g −1, of which mesostructures could be further controlled by a heat-treatment at 250–350 °C without collapse of macrostructures and monolithic forms. When the as-dried gel was heated at 300 °C, the resultant gel transformed to crystalline α-Fe2 O3 and exhibited a specific surface area of 124 m 2 g −1 . Heat-treatment at 350 °C resulted in the broadened size distribution of mesopores. The adsorption behavior of Congo red has revealed that the interconnected macroporous structure contributed to faster diffusion and better accessibility in a continuous flow-through set up, and the crack-free monolithic forms accounted for an advantageous use of the flow-through adsorbents.